Análise e estudo da corrosão em estruturas de concreto armado: estudo de caso - Fernandes, Anábia Vitória (Universidade Federal Rural do Semi-Árido, 2019)
The corrosion in reinforced concrete reinforcement, refers to the some factors of loss or decline occurrence in related to the structure. In majority of cases is related to the performance of a product or structural component. The present study deals with the analysis and study of these demonstrations in a residential social use building, located in São Miguel-RN city. Consists of a literature review and a survey of photography datas, which situation identification, in order to check possible causes, recognize type and corrosion forms, subsequently, diagnoses a form of prevention and recovery as a solution, with the help of triangle of corrosion. We understand through this research, that manifestation pathologicals result from the lack of inspection and maintenance, this way, to have greater durability of buildings is necessary a constant fulfillment of inspection/maintenance, permitting the completion of the intended service life and, avoiding, this way, the collapse of every structure, such as in this study.
Keywords: Corrosão; Estrutura; Manifestações patológicas; Inspeção; Triângulo da corrosão; Corrosion; Structure; Pathological manifestations; Inspection; Triangle of corrosion; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA